Public sector Initiatives in Youth Entrepreneurial Development in Ghana - Issues Emerging - Issifu, Amadu Abdulai (Archives of Business Research, 2018)
The purpose of this study was to assess the effectiveness of the Skills Training and Employment Placement (STEP) Programme in leveraging participants’ entrepreneurial skills. It focused on the perceptions of the youth about the programme. The research design used for the study was evaluative. The stratified random sampling technique was used to select 152 respondents out of a population of 200 youth who participated in the programme in some districts in Northern Ghana from September to September, 2005. A questionnaire and interview schedules were used to gather the data for the study. The findings indicated that the programme helped the respondents to acquire the necessary skills for personal growth and development. It was, however, revealed that proper recruitment procedures were not adhered to. Based on the findings of the study, it was recommended that, in order to sustain youth development intervention programmes, the Ministry of Manpower Development, Youth and Employment should: forge partnerships with small-scale businesses and micro enterprises that are interested in youth development programmes and come out with a comprehensive youth development policy to serve as a blueprint for competency-based training in the country.